Physician Anxiety and Burnout: Symptom Correlates and a Prospective Pilot Study of App-Delivered Mindfulness Training - Roy, Alexandra; Druker, Susan; Hoge, Elizabeth A; Brewer, Judson A (JMIR Publications, 2020)
BackgroundPhysician burnout is on the rise, yet little is known about its relationship to anxiety. Mindfulness-based stress reduction has demonstrated decreases in anxiety, yet physicians have reported reluctance to engage in it due to significant time commitments. ObjectiveThe aims of this study are to assess whether app-based mindfulness training can reduce anxiety in physicians and to explore if anxiety and burnout are correlated, thus leading to a reduction in both anxiety and burnout. MethodsThis was a nonrandomized pilot study comprised of 34 physicians who worked in a large US health care network and reported having anxiety. The intervention was an app-based mindfulness program. The main outcome measure was anxiety, measured by the Generalized Anxiety Disorder-7 (GAD-7). The secondary outcome measures assessed burnout: cynicism and emotional exhaustion items from the Maslach Burnout Inventory. ResultsGAD-7 scores decreased significantly at posttreatment (1 month after treatment initiation, 48% reduction, P<.001) and at the 3-month follow-up (57% reduction, P<.001). There was a significant correlation between anxiety and burnout (cynicism: r=.43; P=.01; emotional exhaustion: r=.71; P<.001). There was also a significant decrease in cynicism (50% reduction, P=.003 at posttreatment; 50% reduction, P=.009 at follow-up) and emotional exhaustion at both time points (20% reduction, P<.001 at posttreatment; 20% reduction, P=.003 at follow-up). ConclusionsThis pilot study is the first to test an app-based mindfulness training program targeted at reducing anxiety with physicians and to demonstrate that in physicians, anxiety is correlated with burnout. These findings suggest that this may be an effective tool to reduce anxiety and burnout in physicians. Trial RegistrationClinicalTrials.gov NCT04137081; https://www.clinicaltrials.gov/ct2/show/NCT04137081